Detroit Longitudinal Study, 1967 - Aberbach, Joel ([Verlag nicht ermittelbar], 1984)
This survey asked Detroit area residents about satisfaction with their neighborhoods, police relations, racial discrimination, and perceptions of the 1967 riot and its consequences. In addition, the questionnaire measured feelings of political efficacy, political involvement, evaluations of various political personalities and social programs, and respondents' personal values and aspirations. Respondents' attitudes toward race relations were examined in a series of questions dealing with integration and separation of the races and an open-ended question that prompted respondents to define "Black power." Also included in this study are three derived measures: a general trust scale, an index assessing respondents' interpretations of the riot, and a political power index measuring respondents' perceptions of their ability to affect local and national laws. Questions also elicited background information, such as composition of respondents' parental families, level of education of parental figures, father's occupation, and parental influence on the respondents' job choices. Region and size of place of residence during childhood were also ascertained, as well as how long the respondent had lived in Detroit. Demographic data include age, sex, race, marital status, education and technical training, occupation, employment history, union membership, and service in the Armed Forces for the head of household. In all cases Black respondents were interviewed by Black interviewers and white respondents were interviewed by white interviewers.